The unified protocol for transdiagnostic treatment of emotional disorders for misophonia: a pilot trial exploring acceptability and efficacy - McMahon, Kibby; Cassiello-Robbins, Clair; Greenleaf, Anna; Guetta, Rachel; Frazer-Abel, Emily; Kelley, Lisalynn; Rosenthal, M. Zachary (Frontiers in Psychology, 2024)
Misophonia is a recently defined disorder characterized by distressing responses to everyday sounds, such as chewing or sniffling. Individuals with misophonia experience significant functional impairment but have limited options for evidence-based behavioral treatment. To address this gap in the literature, the current pilot trial explored the acceptability and efficacy of a transdiagnostic cognitive-behavioral approach to treating symptoms of misophonia. This trial was conducted in two studies: In Study 1, the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders (UP) was delivered to eight patients in order to receive feedback to guide revisions to the treatment to suit this population. In Study 2, ten patients received the revised UP treatment to explore its acceptability and preliminary efficacy.This study used a single-case experimental design with multiple baselines, randomizing patients to either a 2-week baseline or 4-week baseline prior to the 16 weeks of treatment, followed by four weeks of follow-up. The findings from these studies suggested that patients found both the original and adapted versions of the UP to be acceptable and taught them skills for how to manage their misophonia symptoms. Importantly, the findings also suggested that the UP can help remediate symptoms of misophonia, particularly the emotional and behavioral responses. These findings provide preliminary evidence that this transdiagnostic treatment for emotional disorders can improve symptoms of misophonia in adults.